Tourism Development Strategy of Buntula'bi Balusu Sub-Village, North Toraja Regency Based on Tourist Perception - Sesaryo Timang, Vica Vanessa; Antariksa, Antariksa; Dwi Ari, Ismu Rini (Journal of Indonesian Tourism and Development Studies, 2014)
Buntula'bi Balusu Sub-village located in North Toraja Regency. It is uniquely endowed with diverse cultural heritages, both physical (tangible) and non-physical (intangible) cultures, viable to attract domestic and/or international tourists. The objectives of this research were to identify Buntula'bi physical and non-physical characteristics, analyse the tourists' perceptions towards Buntula'bi's tourism objects performances, and formulate the appropriate direction of tourism development within the sub-village. The research employed descriptive and evaluative analytical methods through observations on primary data, questionnaires, documentation, and a set of literature reviews. An evaluative approach was used to measure tourists' level of satisfaction towards the tourism objects performances. Tourism component variables were assessed using Importance Performance Analysis (IPA). Descriptively, the physical characteristics in the study site were in the form of ancestral buildings, which included tongkonan Kollo-Kollo, tongkonan Rantewai, togkonan Lingkasile, alang, banuabugi', and also traditional buildings of kombongan, rantetendan, ranteissun, liangtondon, lokkotarra, and sawahadat. Meanwhile, the non-physical characteristics were identified as indigenous traditions in the forms of tribal cultures and ceremonies such as Aluk Todolo, Rambu Solo' and RambuTuka'. The IPA result showed that the top priority for the tourism development strategy in Buntula'bi was to improve public facilities, optimize road conditions, and develop restaurants and accommodation, as well as souvenir shops in Buntula'bi Balusu Sub-Village. Keywords: Importance Performance Analysis, Tourism Development, Toraja